Golden Agri resources and sustainability - Richards, Kenneth; Bach, David (London : SAGE Publications Ltd, 2017)
While the use of palm oil has been documented since ancient times, it is only in the past few decades that this tropical product has taken off in the international market. An invisible component of many products, palm oil can be found in cookies, in chocolates, in soaps, in shampoos, and even in biofuel. This wide range of uses has stimulated cultivation and oil extraction; annual global production has increased more than nine-fold since 1980. By the 2000s, palm oil had become the most heavily traded edible oil in the world.
Originally published: Richards, K., & Bach, D. (2013). Golden Agri resources and sustainability. Golden Network Case 101-13. New Haven, CT: Yale School of Management, Yale University. Retrieved from: https://nexus.som.yale.edu/goldenagri/.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Golden-Agri Resources; Palm oil industry -- Singapore -- Case studies; Oil palm -- Technological innovations -- Singapore -- Case studies